Clinical features and diagnostic evaluation of 83 biopsy-proven sarcoid uveitis cases. Issue 10 (2nd April 2015) - Febvay, Camille; Kodjikian, Laurent; Maucort-Boulch, Delphine; Perard, Laurent; Iwaz, Jean; Jamilloux, Yvan; Broussolle, Christiane; Burillon, Carole; Seve, Pascal
Abstract : Aims: To determine the clinical features of patients with uveitis with biopsy-proven sarcoidosis, document differences in these features according to ethnicity, age and sex, and assess the diagnostic value of biochemical and imaging examinations. Methods: Retrospective study of 83 biopsy-proven sarcoid uveitis cases seen at two Departments of Internal Medicine and two Departments of Ophthalmology between April 2004 and March 2014. Results: Caucasian patients presented with uveitis at a later age than non-Caucasian (58 years vs 41 years; p=0.001) and had more often a chronic form (78.3% vs 43.8%; p=0.01). Women had higher rates of chronic macular oedema than men (48.3% vs 14.3%; p=0.01). There were no statistically significant differences between patients aged ≤50 years and patients aged >50 years. ACE levels were high (>62 U/L) in 61.7% and lysozyme levels high (>16.7 mg/L) in 83.9% of tested patients. Chest X-rays and CTs were suggestive of sarcoidosis in 62.8% and 91.2% of cases, respectively. Among 21 patients with positive tomography and negative X-rays, 13 were Caucasian women >50 years. Endoscopic ultrasound-guided fine-needle aspiration of intrathoracic nodes contributed to the diagnosis in 7 patients with normal labial salivary gland and transbronchial biopsies. Any of the enzyme tests together with any of the imaging tests identified 100% of the patients. Conclusions: In this largest European series of biopsy-proven sarcoidosis to date, the outstanding diagnostic ability of enzyme test plus imaging test couple suggests that the recourse to invasive procedures should be limited to patients with ocular involvement that would justify systemic treatments.